A presença de elementos interdisciplinares entre Astronomia, Meteorologia e Biologia na BNCC e uma proposta de melhoria para trilhas ecológicas - Custodio, Alessandra Goulart [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Technological and scientific development contributed to the modernization of current societies, but during this process the intense and unbalanced exploitation of natural resources had serious consequences for the environment. Future generations play an important role in facing socio-environmental challenges, so the school is fundamental in this sense to train young people capable of thinking critically and transforming the space where they live. Considering the complexity of these challenges and their interdisciplinary characteristics, education needs to establish relationships between the different areas of knowledge. The BNCC is a document that guides education in Brazil today. In this sense, this work intends to identify the elements present in this document that articulates, in an interdisciplinary way, Astronomy, Meteorology and Biology, limiting the investigation between the Final Years of Elementary School and High School. In addition, a proposal for a pedagogical activity will be presented using gamification and an interdisciplinary approach, as tools for teaching on ecological trails. To carry out the analysis of the interdisciplinary elements of the sciences focused on in this work, the methodology used was the categorical analysis technique, developed by Bardin on content analysis. The results obtained from the categorical analysis, allowed us to conclude that from the Final Years of Elementary School to High School, the BNCC reduces by half the skills with interdisciplinary aspects between Astronomy, Meteorology and Biology, presenting a significant lag from this reform made in the High school.

O desenvolvimento tecnológico e científico contribuiu para a modernização das sociedades atuais, porém durante esse processo a exploração intensa e desequilibrada dos recursos naturais gerou graves consequências para o meio ambiente. As futuras gerações possuem papel importante para enfrentar os desafios socioambientais, por isso a escola é fundamental nesse sentido para formar jovens capazes de pensar criticamente e transformar o espaço onde vivem. Considerando a complexidade destes desafios e suas características interdisciplinares, a educação necessita estabelecer relações entre as diversas áreas do conhecimento. A BNCC é um documento que norteia a educação no Brasil atualmente. Neste sentido, este trabalho pretende identificar os elementos presentes nesse documento que articule, de forma interdisciplinar, a Astronomia, Meteorologia e Biologia, limitando a investigação entre os Anos Finais do Ensino Fundamental e Ensino Médio. Além disso, será apresentada uma proposta de atividade pedagógica utilizando de gamificação e de uma abordagem interdisciplinar, como ferramentas para o ensino em trilhas ecológicas. Para realizar a análise dos elementos interdisciplinares das ciências focadas neste trabalho, a metodologia utilizada foi a técnica de análise categorial, elaborada por Bardin sobre análise de conteúdo. Os resultados obtidos a partir da análise categorial, permitiram concluir que dos Anos Finais do Ensino Fundamental para o Ensino Médio, a BNCC reduz pela metade as habilidades com aspectos interdisciplinares entre Astronomia, Meteorologia e Biologia, apresentando uma defasagem significativa a partir dessa reforma feita no Ensino Médio.
The presence of interdisciplinary elements between Astronomy, Meteorology and Biology at BNCC and a proposal for improvement for ecological trails
Keywords: Interdisciplinarity; Trails; Education; Gamification; Gamificação; BNCC; Ensino; Abordagem interdisciplinar do conhecimento; Trilhas; Ensino